Aqueous Solubility Enhancement for Bioassays of Insoluble Inhibitors and QSPR Analysis: A TNF-α Study. (January 2018) - Mettou, Anthi; Papaneophytou, Christos; Melagraki, Georgia; Maranti, Anna; Liepouri, Fotini; Alexiou, Polyxeni; Papakyriakou, Athanasios; Couladouros, Elias; Eliopoulos, Elias; Afantitis, Antreas; Kontopidis, George
The aim of this study is to improve the aqueous solubility of a group of compounds without interfering with their bioassay as well as to create a relevant prediction model. A series of 55 potential small-molecule inhibitors of tumor necrosis factor–alpha (TNF-α; SPD304 and 54 analogues), many of which cannot be bioassayed because of their poor solubility, was used for this purpose. The solubility of many of the compounds was sufficiently improved to allow measurement of their respective dissociation constants (Kd ). Parameters such as dissolution time, initial state of the solute (solid/liquid), co-solvent addition (DMSO and PEG3350), and sample filtration were evaluated. Except for filtration, the remaining parameters affected aqueous solubility, and a solubilization protocol was established according to these. The aqueous solubility of the 55 compounds in 5% DMSO was measured with this protocol, and a predictive quantitative structure property relationship model was developed and fully validated based on these data. This classification model separates the insoluble from the soluble compounds and predicts the solubility of potential small-molecule inhibitors of TNF-α in aqueous solution (containing 5% DMSO as co-solvent) with an accuracy of 81.2%. The domain of applicability of the model indicates the type of compounds for which estimation of aqueous solubility can be confidently predicted.